Effects of a mutual recovery intervention on mental health in depressed elderly community-dwelling adults: a pilot study - Wang, Chao; Hua, Yujie; Fu, Hua; Cheng, Longfeng; Qian, Wen; Liu, Junyang; Crawford, Paul; Dai, Junming (BioMed Central, 2017)
Background